Potential Therapies to Protect the Aging Heart Against Ischemia/Reperfusion Injury - Díaz-Vesga, Magda C.; Zúñiga-Cuevas, Úrsula; Ramírez-Reyes, Andrés; Herrera-Zelada, Nicolas; Palomo, Iván; Bravo-Sagua, Roberto; Riquelme, Jaime A. (Frontiers in Cardiovascular Medicine, 2021)
Despite important advances in the treatment of myocardial infarction that have significantly reduced mortality, there is still an unmet need to limit the infarct size after reperfusion injury in order to prevent the onset and severity of heart failure. Multiple cardioprotective maneuvers, therapeutic targets, peptides and drugs have been developed to effectively protect the myocardium from reperfusion-induced cell death in preclinical studies. Nonetheless, the translation of these therapies from laboratory to clinical contexts has been quite challenging. Comorbidities, comedications or inadequate ischemia/reperfusion experimental models are clearly identified variables that need to be accounted for in order to achieve effective cardioprotection studies. The aging heart is characterized by altered proteostasis, DNA instability, epigenetic changes, among others. A vast number of studies has shown that multiple therapeutic strategies, such as ischemic conditioning phenomena and protective drugs are unable to protect the aged heart from myocardial infarction. In this Mini-Review, we will provide an updated state of the art concerning potential new cardioprotective strategies targeting the aging heart.